2017
DOI: 10.1002/ijgo.12086
|View full text |Cite
|
Sign up to set email alerts
|

A hospital‐based study of intimate partner violence during pregnancy

Abstract: IPV was documented in approximately 12% of participants. Population-based surveys need to be done to investigate further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 15 publications
7
25
2
1
Order By: Relevance
“…Other research in SSA found physical IPV in pregnancy rates of 22.5%, 22% and 9% in Nigeria, 10.7% in Tanzania and 36% in South Africa 22–25. Similar studies in other low resource settings such as India (12%) and Bangladesh (35.2%) reveal much lower rates of physical IPV in pregnancy than reported in SSA,26 with the exception of a single study in Bangladesh 27. Training of research staff and the setting may affect the answers given on IPV questions and contribute to variability of results.…”
Section: Discussionsupporting
confidence: 63%
“…Other research in SSA found physical IPV in pregnancy rates of 22.5%, 22% and 9% in Nigeria, 10.7% in Tanzania and 36% in South Africa 22–25. Similar studies in other low resource settings such as India (12%) and Bangladesh (35.2%) reveal much lower rates of physical IPV in pregnancy than reported in SSA,26 with the exception of a single study in Bangladesh 27. Training of research staff and the setting may affect the answers given on IPV questions and contribute to variability of results.…”
Section: Discussionsupporting
confidence: 63%
“…Forty-one studies (82%, n = 41) were of high methodological quality (indicating low risk of bias) ( Table 2). [18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34][35][36][37][38][39][40][41]43,[46][47][48][49][51][52][53][56][57][58][59][60][61][62][63][65][66][67] Most of the studies with high or moderate risk of bias obtained low scores in sample selection 30,45,50,54,55,64 or comparability. 27,45,50,…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
“…Pre-term birth or prematurity A total of 20 studies with high methodological quality looked at pre-term birth (Table S1). [18][19][20][21]24,[31][32][33]35,37,38,46,49,53,[57][58][59][60]63,67 Four of them found a significant association with undifferentiated IPV, 33,46,49,57 six with physical IPV, 32,33,37,53,57,59 and only one with psychological IPV. 57 The risk of pre-term birth was between 1.97 and 5.94 times higher among women who had experienced undifferentiated IPV, and between 2.29 and 5.7 times higher among those who experienced physical IPV.…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations